Ghrelin Protection against Lipopolysaccharide-Induced Gastric Mucosal Cell Apoptosis Involves Constitutive Nitric Oxide Synthase-Mediated Caspase-3 S-Nitrosylation - Bronislaw L. Slomiany; Amalia Slomiany (Hindawi Limited, 2010)
Ghrelin, a peptide hormone produced mainly in the stomach, has emerged as an important modulator of the inflammatory responses that are of significance to the maintenance of gastric mucosal integrity. Here, we report on the role of ghrelin in controlling the apoptotic processes induced in gastric mucosal cells by H. pylori lipopolysaccharide (LPS). The countering effect of ghrelin on the LPS-induced mucosal cell apoptosis was associated with the increase in constitutive nitric oxide synthase (cNOS) activity, and the reduction in caspase-3 and inducible nitric oxide synthase (NOS-2). The loss in countering effect of ghrelin on the LPS-induced changes in apoptosis and caspase-3 activity was attained with Src kinase inhibitor, PP2, as well as Akt inhibitor, SH-5, and cNOS inhibitor, L-NAME. Moreover, the effect of ghrelin on the LPS-induced changes in cNOS activity was reflected in the increased cNOS phosphorylation that was sensitive to SH-5. Furthermore, the ghrelin-induced up-regulation in cNOS activity was associated with the increase in caspase-3 S-nitrosylation that was susceptible to the blockage by L-NAME. Therefore, ghrelin protection of gastric mucosal cells against H. pylori LPS-induced apoptosis involves Src/Akt-mediated up-regulation in cNOS activation that leads to the apoptotic signal inhibition through the NO-induced caspase-3 S-nitrosylation.